2020
DOI: 10.1136/bmjopen-2019-031670
|View full text |Cite
|
Sign up to set email alerts
|

Is telehealthcare for heart failure patients cost-effective? An economic evaluation alongside the Danish TeleCare North heart failure trial

Abstract: ObjectiveThis study aimed to assess the cost-effectiveness of telehealthcare in heart failure patients as add-on to usual care.DesignA cost-utility analysis was conducted from a public payer perspective alongside the randomised controlled TeleCare North trial.SettingThe North Denmark Region, Denmark.ParticipantsThe study included 274 heart failure patients with self-reported New York Heart Association class II-IV.InterventionsPatients in the intervention group were provided with a Telekit consisting of a table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…Telemedicine nowadays coexists alongside conventional healthcare in most healthcare systems [1]. Although systematic reviews of its economic impact suggest that, for the time being, it is not suited to widespread implementation in all specialties and contexts [2,3], recent studies suggest that it is cost-effective in fields such as emergency medicine, cardiology, the management of diabetes and ophthalmology [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine nowadays coexists alongside conventional healthcare in most healthcare systems [1]. Although systematic reviews of its economic impact suggest that, for the time being, it is not suited to widespread implementation in all specialties and contexts [2,3], recent studies suggest that it is cost-effective in fields such as emergency medicine, cardiology, the management of diabetes and ophthalmology [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 6 , 7 ] TM reduces healthcare professionals’ burden and patients’ risks, and contributes to reducing costs. [ 2 7 , 9 15 , 21 25 ]…”
Section: Telemedicine In Heart Failure: Remote Patient Managementmentioning
confidence: 99%
“…The high costs associated with HF – mainly derived from HF hospitalisations – which can be mitigated by TM. [ 2 , 3 , 14 , 15 , 21 25 ]…”
Section: The Digital Transformation Of Heart Failure Carementioning
confidence: 99%
“…A research report on the economic impact of this monitoring system has concluded that it is highly cost-effective for the treatment of patients with heart failure. Significant cost savings were identified in relation to hospitalisations, primary care contacts, and total expenditure (Vestergaard et al, 2020).…”
Section: Remote Monitoringmentioning
confidence: 99%